The mutual interactions among Helicobacter pylori, chronic gastritis, and the gut microbiota: a population-based study in Jinjiang, Fujian - Li, Hanjing; Hu, Yingying; Huang, Yanyu; Ding, Shanshan; Zhu, Long; Li, Xinghui; Lan, Meng; Huang, Weirong; Lin, Xuejuan (Frontiers in Microbiology, 2024)
Helicobacter pylori (H. pylori) is a type of bacteria that infects the stomach lining, and it is a major cause of chronic gastritis (CG). H. pylori infection can influence the composition of the gastric microbiota. Additionally, alterations in the gut microbiome have been associated with various health conditions, including gastrointestinal disorders. The dysbiosis in gut microbiota of human is associated with the decreased secretion of gastric acid.Chronic atrophic gastritis (CAG) and H. pylori infection are also causes of reduced gastric acid secretion. However, the specific details of how H. pylori infection and CG, especially for CAG, influence the gut microbiome can vary and are still an area of ongoing investigation. The incidence of CAG and infection rate of H. pylori has obvious regional characteristics, and Fujian Province in China is a high incidence area of CAG as well as H. pylori infection. We aimed to characterize the microbial changes and find potential diagnostic markers associated with infection of H. pylori as well as CG of subjects in Jinjiang City,